2018
DOI: 10.33736/jcshd.1122.2018
|View full text |Cite
|
Sign up to set email alerts
|

Generation-Y Employees and Their Perceptions of Work-Life Balance

Abstract: The objective of this study is to identify the perceptions of Generation Y employees regarding work-life balance practices. As increasing numbers of Generation Y enter the workforce, questions regarding how they perceive work, family and self-related issues, challenges and coping strategies in balancing personal and professional commitments became issues of interests for employers. This study uses interviews to collect data from six informants in Generation Y and the data were analyzed through content analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Other things they considered as important were money, happiness, and integrity, honesty, and truthfulness. In contrast, the values listed in literature as the main "pillars" of the inner world of a statistical "Y" are on the one hand personal and affiliation values, such as family life, happiness, love, and friendship, and on the other hand a well-paid job, treated as a prerequisite for a prosperous, pleasant, and interesting life and as a source of personal satisfaction (Yeaton, 2008;Stanimir, 2015;Mos et al, 2018).…”
Section: Discussion Of Study Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other things they considered as important were money, happiness, and integrity, honesty, and truthfulness. In contrast, the values listed in literature as the main "pillars" of the inner world of a statistical "Y" are on the one hand personal and affiliation values, such as family life, happiness, love, and friendship, and on the other hand a well-paid job, treated as a prerequisite for a prosperous, pleasant, and interesting life and as a source of personal satisfaction (Yeaton, 2008;Stanimir, 2015;Mos et al, 2018).…”
Section: Discussion Of Study Resultsmentioning
confidence: 99%
“…This does not mean, however, that the representatives of Generation Y are ready to resign from achievements and associated awards; on the contrary -they seem less patient waiting to be awarded, expecting their contributions to be accepted and appreciated. Despite high expectations regarding remuneration and recognition of achievements, it can be stated that the representatives of Generation Y pay more attention to the conditions and process of achieving achievement and are less willing to sacrifice other spheres of life for work (Winter and Jackson, 2016;Mos et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lee et al [30] reported that employees' positive experiences in work life positively predicts one's life satisfaction especially when they faced less work-family life conflicts, which indicated that employees heavily emphasized on achieving work life balance in their jobs. This could be clearly seen in Mos [31] study, where employees mentioned their commitment in managing their time to achieve the balance between work and family.…”
Section: "Felt Angry and Exasperated When I Was Doing My Internship B...mentioning
confidence: 93%